Enteric motor dysfunctions in experimental chronic pancreatitis: Alterations of myenteric neurons regulating colonic motility in rats. Issue 7 (9th March 2018) - Chen, L.; Yu, B.; Luo, D.; Lin, M.
Abstract: Background: The mechanism underlying gastrointestinal (GI) dysmotility associated with chronic pancreatitis (CP) has not been fully elucidated, and enteric nervous system (ENS) has an important regulatory role in gastrointestinal motor function. The aim of this study is to investigate the effect of ENS in the colonic hypomotility induced by trinitrobenzene sulfonic acid (TNBS) infusion which mimics CP. Methods: Male Sprague‐Dawley rats were submitted to CP which was induced by pancreatic infusion of 2% TNBS, or sham group with treatment of equal saline. Three weeks after induction of CP, we pathologically examined the inflammation of pancreas and counted the number of withdrawal events stimulated by Von Frey filaments to evaluate hyperalgesia. The gastrointestinal transit rate was measured using Carbon inkl driving test, and the contraction activities of colonic muscle strip were studied in an organ bath system. The expression of choline acetyltransferase (ChAT) and nitric oxide synthase (NOS) in colonic myenteric plexus (MP) of ENS were investigated by Western blotting and double immunofluorescence staining. Key Results: In TNBS‐treated group, rats had the signs of chronic pancreatitis 3 weeks after intraductal infusion and had increased sensitivity to mechanical stimulation of the abdomen. For rats with CP, the gastrointestinal transit rate was reduced; in addition, the contractile activities of longitudinal muscle (LM) and circular muscle (CM) strips of distal colon in TNBS group were lower than those in sham group. Immunofluorescence demonstrated that the percentage of ChAT‐immunoreactive (IR) neurons in the MP was decreased, but the proportion of NOS‐IR neurons in the MP was increased when compared with sham‐operated group. Western blotting proved that TNBS infusion down‐regulated ChAT but up‐regulated NOS expression in the colon MP. Conclusions & Inferences: Decreased ChAT‐IR neurons and increased NOS‐IR in the MP of colon ENS may contribute to the pathogenesis of colonic dysmotility in CP. Abstract : Chronic pancreatitis (CP) is regarded to be an irreversible progressive chronic inflammatory disorder, which is complicated by gastrointestinal dysmotility in some cases. Decreased ChAT‐IR neurons and increased NOS‐IR in the MP of colon ENS may contribute to the pathogenesis of colonic dysmotility in CP.